2017
DOI: 10.1080/02699052.2017.1300836
|View full text |Cite
|
Sign up to set email alerts
|

A review of the evidence of zolpidem efficacy in neurological disability after brain damage due to stroke, trauma and hypoxia: A justification of further clinical trials

Abstract: During 15 years, 23 clinical reports and 6 studies have demonstrated associations between sub-sedative doses of zolpidem and recoveries from brain damage due to strokes, trauma and hypoxia. Clinical findings include unexpected awakenings from vegetative states and regressions of stroke symptoms after dosing that disappear during elimination and reappear on repeat dosing. Initially single-photon emission computed tomography scans showed improved perfusion within, around and distant from infarctions. Then positr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…Are some patients just below this critical threshold? Different interventions, such as zolpidem or amantadine administration 65 , 66 , thalamic stimulation with deep brain stimulation 62 or low-intensity focused ultrasound pulsation 63 , transcranial direct current stimulation 67 , and vagal nerve stimulation 68 have demonstrated significant behavioral improvements in individual patients but a reliable read-out and interpretation of their end-point effects at the level of cortical circuits is still lacking. In the view of the present results, detecting the presence of cortical sleep-like bistability and tracking its evolution over time, may offer an objective reference to devise, guide, and titrate therapeutic strategies aimed at restoring consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Are some patients just below this critical threshold? Different interventions, such as zolpidem or amantadine administration 65 , 66 , thalamic stimulation with deep brain stimulation 62 or low-intensity focused ultrasound pulsation 63 , transcranial direct current stimulation 67 , and vagal nerve stimulation 68 have demonstrated significant behavioral improvements in individual patients but a reliable read-out and interpretation of their end-point effects at the level of cortical circuits is still lacking. In the view of the present results, detecting the presence of cortical sleep-like bistability and tracking its evolution over time, may offer an objective reference to devise, guide, and titrate therapeutic strategies aimed at restoring consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Are some patients just below this critical threshold? Different interventions (73), such as zolpidem or amantadine administration(74,75), thalamic stimulation with Deep Brain Stimulation(69,76) or low-intensity focused ultrasound pulsation(70), transcranial direct current stimulation(77,78) and vagal nerve stimulation(79) have demonstrated significant behavioural improvements in individual patients but a reliable read--out and interpretation of their end--point effects at the level of cortical circuits is still lacking. To the extent that sleep--like bistability represents the common functional endpoint of loss of complexity in severely brain--injured brains, detecting…”
mentioning
confidence: 99%
“…Awakening, a temporary revival of patients who have been akinetic, apathic and with no reaction for years following a large brain damage, has been observed after administration of drugs even if the mechanisms underlying them remain unknown. Although rare, the awakenings produced briefly by "sleeping pills" are now well documented [1][2][3]. Arnst et al recently reported spectacular effects of Benzodiazepines (BZDs) on a 29 years old patient after a severe hypoxic-ischemic brain injury and following a history of alcohol abuse [4].…”
Section: Introductionmentioning
confidence: 99%